Clients’ Satisfaction of the Therapeutic Community Modality Program: Basis for the Development of Prototype Syllabus - Virtudazo, Francia; Dausan, Alrien (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study determined the Therapeutic Community (TC) clients’ satisfaction and assessment of the Therapeutic Community Modality Program rendered by the Parole and Probation Administration in the National Capital Region. Researchers-made survey questionnaire was administered to two (2) groups of respondents which comprise the subject population of the research. The study revealed that the TC clients were satisfied on the Therapeutic Community Modality Program in all of the dimensions being assessed; however, there are indicators on clients’ satisfaction that obtained the lowest weighted mean that need to be addressed. On behavior management, there is a need for the TC implementers to reinforce community values and give emphasis on organizational structure. Moreover, the TC implementers must give preferential attention on the application of the full program of mandatory daily activities and meetings. On the intellectual and spiritual aspects, educational activities such as seminars on special topics and academic training must be intensified with focus on group activities that counter negative behavior to reinforce community values. On vocational and survival aspects, the TC program must incorporate vocational and livelihood training. Furthermore, clients must be taught to control their actions and release them appropriately. On emotional and psychological aspects, the TC clients must be encouraged to ‘act as if’ as a means of developing a more positive attitude. In addition, self-help technique must be inculcated throughout the program and accelerated before re-entry of the clients to the community.